Preferensi Konsumen Mahasiswa Sekolah Vokasi IPB terhadap Keputusan Pembelian Kopi Vokasi dan Prolog Kopi - Doni Sahat Tua Manalu; Rahmawati Liswahyuni Dwi Wardhani; Queen Fadilla Melawardani; Suci Hakimah; Bulan Wiranata Septiani Tambunan; Zakwan Zaky Bahara Simbolon (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Coffee purchases in Bogor City are not only influenced by product quality and price, but are also influenced by people's needs for coffee products. This research aims to 1) determine consumer preferences in purchasing coffee 2) determine the most dominant attributes based on the highest ranking of consumer attitude values in purchasing decisions for Vocational Coffee and Prolog Coffee. This research was carried out using the questionaire method. The sample in this study was 100 respondents, especially IPB Vocational School students. Fishbein multiattribute analysis is used in this research to calculate the usefulness value and relative importance of each attribute. . The research results show that coffee consists of 7 attributes, namely taste, flavor variants, product packaging, product quality, product price, product facilities and coffee shop service. The attribute that is considered the most important by respondents who buy coffee at Kopi Vokasi and Prolog Kopi is in accordance with the attitude value (Ao) in attribute (1) taste of 20.07 which shows the attribute value results are 'positive'.